The contents and distributions of cadmium, mercury, and lead in Usnea antarctica lichens from Solorina Valley, James Ross Island (Antarctica) - Zvěřina, Ondřej; Coufalík, Pavel; Barták, Miloš; Petrov, Michal; Komárek, Josef (Environmental monitoring and assessment, 2017)
Lichens are efficient and cost-effective biomonitors of the environment. Their geographic distribution together with their slow growth rate enable investigation of the deposition patterns of various elements and substances. In this research, levels of cadmium, lead, and mercury in Usnea antarctica lichens in the area of James Ross Island, Antarctica, were investigated. The lichens were microwave-digested, and the metals were determined by means of atomic absorption spectrometry with graphite furnace and a direct mercury analyzer. Median total contents of Cd, Hg, and Pb were 0.04, 0.47, and 1.6 mg/kg in whole lichens, respectively. The bottom-up distributions of these metals in the fruticose lichen thalli were investigated, and it was revealed that the accumulation patterns for mercury and lead were opposite to that for cadmium. The probable reason for this phenomenon may lie in the inner structure of thalli. The total contents of metals were comparable with those published for other unpolluted areas of maritime Antarctica. However, this finding was not expected for mercury, since the sampling locality was close to an area with some of the highest mercury contents published for Antarctic lichens. In short, lichens proved their usability as biological monitors, even in harsh conditions. However, the findings emphasize the need to take into account the distributions of elements both in the environment and in the lichen itself.
Keywords: Lichen; Spectrophotometry, Atomic; chinolony; Ascomycota; Quinolones; olovo; kadmium; Antarctica; monitorování životního prostředí; Cadmium; Metals; Heavy metals; rtuť; kovy; lišejníky; spektrofotometrie atomová; ostrovy; Lead; Mercury; Islands; Air Pollutants; Antarktida; Antarctic Regions; Environmental Monitoring; Lichens; Biomonitoring; látky znečišťující vzduch; Usnea